2018
DOI: 10.14411/fp.2018.016
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdochona angusticaudata sp. n. (Nematoda: Rhabdochonidae) from the Japanese eel Anguilla japonica, and new records of some other nematodes from inland fishes in Japan

Abstract: The new species, R. angusticaudata sp. n., described from the intestine of the Japanese eel Anguilla japonica Temminck et Schlegel in the Renjoji River, Shikoku, is mainly characterised by the presence of 14-16 anterior prostomal teeth, non-bifurcated deirids with rounded ends, the length of the left spicule (300-384 µm long), the right spicule with a dorsal barb and non-filamented eggs. The species of Paraquimperia Baylis, 1934 and A. arctica are reported from Japan for the first time. Based on light and scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Morphological identification of infectious fourth stage larvae (L4) is problematic. Moravec and Nagasawa (2018) concluded that L4 stage Eustrongylides are unidentifiable to species by morphological features. In Mazzone et al (2019) , L4 E. ignotus and E .…”
Section: Discussionmentioning
confidence: 99%
“…Morphological identification of infectious fourth stage larvae (L4) is problematic. Moravec and Nagasawa (2018) concluded that L4 stage Eustrongylides are unidentifiable to species by morphological features. In Mazzone et al (2019) , L4 E. ignotus and E .…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic classification of the specimen was conducted based on the morphology outlined by Moravec and Justine (2020). Morphological comparisons among paracapillariid species in the subgenus Ophidiocapillaria were made using information from various sources, including Teixeira de Freitas and Lent (1934), Skryabin et al (1957), Pence (1970), Wang (1982), Biserkov et al (1985), Moravec and Gibson (1986), Moravec (1986), De (1998) and Charoennitiwat et al (2023), with reference examined specimens listed in Table S1.…”
Section: Scanning Electron Microscopy Studymentioning
confidence: 99%
“…Many nematode species have been described in C. punctata however, there is a great deal of taxonomic confusion regarding larval nematodes identified from C. punctata in Bangladesh ( Table 1 ). It is recognised that identification of larval nematodes to a species level morphologically is not reliable ( Borges et al, 2012 ; Shamsi and Suthar, 2016a ; Moravec and Nagasawa, 2018 ; Mazzone et al, 2019 ; Abro et al, 2020 ) because most features are absent in larval specimens. Therefore, the aim of this study was to identify larval nematodes recovered from the intestinal mesentery of C. punctata (Bangladesh) using molecular methodology.…”
Section: Introductionmentioning
confidence: 99%